An unusual species of the genus Pseudohalmyrapseudes Larsen & Hansknecht, 2004 (Tanaidacea: Parapseudidae) from the mangrove swamps of the Cần Giờ Biosphere Reserve, South Vietnam - Marin, Ivan; Palatov, Dmitry; Thịnh, Nguyễn Văn (Zootaxa, 2024)
The article describes a new species of the genus Pseudohalmyrapseudes (Tanaidacea: Parapseudidae: Parapseudinae) found in the cut part of the deep channel of the Cần Giờ Mangrove Biosphere Reserve in South Vietnam. The new species shares morphological features of such parapseudid genera as Pseudohalmyrapseudes including a three- and four-articulated inner ramus of antennule in females and males, respectively, the triangular shape of fixed finger, and the presence of basal tooth on dactylus of cheliped in males. From Halmyrapseudes it is distinguished by the well-marked outer serration on the lobe of labium and the presence of relatively small blunt ventral tooth on carpus of the male cheliped. At the same time, it can be easily separated from any species of these genera by the shape of male cheliped, especially by the triangular shape of fixed finger and the presence of basal process tooth on dactylus, and the absence of plumose ventral setae on merus, carpus and propodus of pereopod VI. The new species is also unusual within the genus Pseudohalmyrapseudes in terms of habitat, as it lives in mangrove swamps rather than freshwater environments, known for congeners, and its distribution area, representing the first species from the Asian region. Based on the calculated density (124±17 inds/m2) and the trophic niche determined by the analysis of stable isotopes δ13C/δ15N, the studied species is considered among important primary consumers (C1), most likely feeding on the leaves of the mangrove Rhizophora apiculata in the studied lagoon.